Neuroserpin expression during human brain development and in adult brain revealed by immunohistochemistry and single cell RNA sequencing - Adorjan, I; Tyler, T; Bhaduri, A; Demharter, S; Finszter, C; Bako, M; Sebok, O; Nowakowski, T; Khodosevich, K; Møllgård, K; Kriegstein, A; Shi, L; et al. (Wiley, 2019)
Neuroserpin is a serine‐protease inhibitor mainly expressed in the CNS and involved in the inhibition of the proteolytic cascade. Animal models confirmed its neuroprotective role in perinatal hypoxia‐ischaemia and adult stroke. Although neuroserpin may be a potential therapeutic target in the treatment of the aforementioned conditions, there is still no information in the literature on its distribution during human brain development. The present study provides a detailed description of the changing spatiotemporal patterns of neuroserpin focusing on physiological human brain development. Five stages were distinguished within our examined age range which spanned from the 7th gestational week until adulthood. In particular, subplate and deep cortical plate neurons were identified as the main sources of neuroserpin production between the 25th gestational week and the first postnatal month. Our immunohistochemical findings were substantiated by single cell RNA sequencing data showing specific neuronal and glial cell types expressing neuroserpin. The characterization of neuroserpin expression during physiological human brain development is essential for forthcoming studies which will explore its involvement in pathological conditions, such as perinatal hypoxia‐ischaemia and adult stroke in human.